Technical schools of the Unified Health System: an analysis of nursing education - Ribeiro-Barbosa, Juliana Costa; Silva, Gilberto Tadeu Reis da; Amestoy, Simone Coelho; Silva, Cristiane Costa Reis da; Silva, Rosana Maria de Oliveira; Backes, Vânia Marli Schubert (Revista da Escola de Enfermagem da USP, 2020)
Objective: To analyze nursing education in the Technical Schools of the Unified Health System in the Northeastern region of Brazil. Method: A documentary study with a qualitative approach, having its locus as Technical Schools of the Unified Health System in the Northeast Region which offer the technical course in nursing. Data sources were the Pedagogical Political Projects of the school and the Teaching Plans of the referred courses, and three structured scripts on the pedagogical aspects of training were used as instruments. The systematization/data analysis was based on thematic content analysis. Results: Technical training in nursing occurs through: an integrative approach, being considered a pedagogical trend; problematizing approach, used as a methodological way for teaching-learning; and qualitative assessment, enhancing the scope of professional skills. Conclusion: The training in focus points to the commitment to the Unified Health System and professional excellence, as it strengthens the integration between teaching-service-community, encourages student proactivity and indicates teaching-learning in the demands of the population and the public health system, and enhances the acquiring and improving professional skills.